Image-guided thermal therapy with a dual-contrast magnetic nanoparticle formulation: A feasibility study. (3rd July 2016) - Attaluri, Anilchandra; Seshadri, Madhav; Mirpour, Sahar; Wabler, Michele; Marinho, Thomas; Furqan, Muhammad; Zhou, Haoming; De Paoli, Silvia; Gruettner, Cordula; Gilson, Wesley; DeWeese, Theodore; Garcia, Monica; et al.
Abstract: Purpose/objective: The aim of this study was to develop and investigate the properties of a magnetic iron oxide nanoparticle–ethiodised oil formulation for image-guided thermal therapy of liver cancer. Materials and methods: The formulation comprises bionised nano-ferrite (BNF) nanoparticles suspended in ethiodised oil, emulsified with polysorbate 20 (BNF-lip). Nanoparticle size was measured via photon correlation spectroscopy and transmission electron microscopy. In vivo thermal therapy capability was tested in two groups of male Foxn1 nu mice bearing subcutaneous HepG2 xenograft tumours. Group I ( n = 12) was used to screen conditions for group II ( n = 48). In group II, mice received one of BNF-lip ( n = 18), BNF alone ( n = 16), or PBS ( n = 14), followed by alternating magnetic field (AMF) hyperthermia, with either varied duration (15 or 20 min) or amplitude (0, 16, 20, or 24 kA/m). Image-guided fluoroscopic intra-arterial injection of BNF-lip was tested in New Zealand white rabbits ( n = 10), bearing liver VX2 tumours. The animals were subsequently imaged with CT and 3 T MRI, up to 7 days post-injection. The tumours were histopathologically evaluated for distribution of BNF-lip. Results: The BNF showed larger aggregate diameters when suspended in BNF-lip, compared to clear solution. The BNF-lip formulation produced maximum tumour temperatures with AMF >20 kA/m and showed positive X-ray visibility and substantial shortening of T1 and T2 relaxation time, with sustained intratumoural retention up to 7 days post-injection. On pathology, intratumoural BNF-lip distribution correlated well with CT imaging of intratumoural BNF-lip distribution. Conclusion: The BNF-lip formulation has favourable thermal and dual imaging capabilities for image-guided thermal therapy of liver cancer, suggesting further exploration for clinical applications.